Pengaruh Komposisi Asupan Makan terhadap Komponen Sindrom Metabolik pada Remaja - Djanggan Sargowo; Sri Andarini (Jurnal Kardiologi Indonesia, 2011)
Obesity as the component of metabolic syndrome and its associated disor-ders are a growing epidemic across the world. Several genetic, behavioral, and physiological factors play a role in etiology of obesity. Behavior factor such as high-carbohydrate and high-fat diet is important as this factor, but not the sedentary factor, is still having possibility to be altered. This study is performed to explain the influence of food intake to the components of metabolic syndrome. The method used is case-control analysis of population-based, epidemiological surveys using the metabolic syndrome definition of International Diabetes Federation. The results suggest that the total cholesterol and waist circumference components have higher pathway co-efficiency than other components. The compositions of food intake causing the metabolic syndrome are total  calories followed by fat and carbohydrate, consecutively. From these results, reduction of total calorie and fat can be recommended as dietary modification that reduces the risk of developing metabolic syndrome.